2017
DOI: 10.1038/am.2017.31
|View full text |Cite
|
Sign up to set email alerts
|

Nano-formulated curcumin accelerates acute wound healing through Dkk-1-mediated fibroblast mobilization and MCP-1-mediated anti-inflammation

Abstract: Turmeric, a product of Curcuma longa, has a very long history of being used for the treatment of wounds in many Asian countries. Curcumin, the principal curcuminoid of turmeric, has recently been identified as a main mediator of turmeric's medicinal properties. However, the inherent limitations of the compound itself, such as hydrophobicity, instability, poor absorption and rapid systemic elimination, pose big hurdles for translation to wider clinical application. We present here an approach for engineering cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(73 citation statements)
references
References 33 publications
7
64
0
1
Order By: Relevance
“…Numerous blood vessels were well‐distributed around the wound bed. Faster angiogenesis and well‐distribution of fibroblasts promoted the rapid growth of granulation tissues that might have led to quicker and better re‐epithelialization …”
Section: Resultsmentioning
confidence: 99%
“…Numerous blood vessels were well‐distributed around the wound bed. Faster angiogenesis and well‐distribution of fibroblasts promoted the rapid growth of granulation tissues that might have led to quicker and better re‐epithelialization …”
Section: Resultsmentioning
confidence: 99%
“…Our previous study demonstrated delayed wound healing of ischaemic/reperfusion skin flaps, which was observed in IL‐6‐deficient mice . Inflammation plays a pivotal role in wound healing, and reducing it might promote the healing processes . Moreover, the use of anti‐inflammatory drugs might be key therapies for enhancing wound healing …”
Section: Discussionmentioning
confidence: 99%
“…29 Inflammation plays a pivotal role in wound healing, and reducing it might promote the healing processes. 1,30 Moreover, the use of anti-inflammatory drugs might be key therapies for enhancing wound healing. 31 One aspect of impaired healing that has received considerable attention is the enhanced and prolonged expression of TNF-α, a potent pro-inflammatory cytokine that contributes to impaired healing.…”
Section: Discussionmentioning
confidence: 99%
“…Gelatin (a mixture of proteins and peptides) is a natural polymer which is biocompatible, nontoxic and biodegradable, and hence is considered as a fair and safe choice when selecting fiber material for dressing problematic wounds such as diabetic chronic ulcers. The light weight ultrathin nanofibers can serve as mechanical support during wound dressings due to their significant tensile strength as compared to conventional fibers (having diameters in the range of over 100 nm) and also act as barriers to cover the wound [30][31][32][33]. Gelatin is also known for its excellent water absorption and fluid affinity, which makes it a good choice to support moist wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…More curcumin would be expected to release with a specific rate from higher concentrations, such as 17% curcumin loaded poly (εcaprolactone) (PCL) nanofibers than the lower concentrations, such as 3% curcumin loaded PCL nanofibers, after 12 h (as shown in figure 2(b)) [30]. Using PCL-curcumin solutions, biofunctional electrospun nanofibers were prepared [30][31][32][33]68]. Hoang et al [68] fabricated curcumin loaded PCL/chitosan nonwoven mats (for wound dressings) using formic acid and acetone together as solvents while electrospinning nanofibers.…”
Section: Introductionmentioning
confidence: 99%